The Effects of Nucleus Accumbens Opiate and Adenosine Receptor Activity on Appetitive Operant Learning - Clissold, Kara Allison (Wake Forest University, 2012)
Learning is an important component of addiction and reward processes. Systemic manipulations of the opioid and adenosine receptor pathways influence learning in several different paradigms. Manipulations of both of these receptors within the nucleus accumbens affect motivational aspects of instrumental conditioning and food intake. The nucleus accumbens has previously been shown to be important for the learning of appetitive instrumental conditioning tasks through NMDA receptor activity (Smith-Roe & Kelley, 2000). The present set of experiments examined the roles of opiate and adenosine receptors in appetitive instrumental conditioning through pharmacological activation and suppression of μ-opioid and adenosine 2A receptors within the rat nucleus accumbens during the first five days of acquisition of an appetitive operant lever-pressing response. Subjects subsequently trained on the operant learning paradigm until lever pressing patterns stabilized and then received another drug injection to test the effects of the drugs on general operant performance. Both activation and blockade of μ-opioid receptors dose-dependently impaired acquisition of the lever press, though only blockade of opiate receptors impaired lever pressing after the task had been learned and impaired nosepoking behavior. Activation of adenosine 2A (A2A) receptors impaired acquisition and performance of the operant task. Blockade of A2A receptors had no effect on either lever pressing or nosepoking behavior during either the learning or performance assessment periods. These novel data suggest that opiate receptors may control appetitive operant learning through two different mechanisms, while adenosine receptors are important in maintaining operant performance.
Keywords: accumbens; adenosine; learning; opiate